2019
DOI: 10.1371/journal.pone.0211786
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in clinical characteristics of invasive group G streptococcal infection: Comparison with group A and group B streptococcal infections

Abstract: Purpose Invasive Group G streptococcal infection (iGGS) has increasingly been recognized as a cause of severe disease, mainly among elderly people with chronic illnesses. This study aimed to examine age-related differences in clinical characteristics of iGGS and describe its characteristics among very elderly individuals (≥80 years). Methods Fifty-four iGGS patients for whom detailed clinical information was available were identified from 2002 to 2014 in a tertiary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Among GGS, SDSE infection is most frequent in humans [5]. While STSS due to GAS can occur in patients without underlying conditions [6], STSS due to GGS tends to occur in elderly patients and those with underlying conditions, such as diabetes mellitus, cardiovascular diseases, malignancies, cirrhosis, immunosuppressive conditions, or skin diseases [5,7,8]. In our case, the causative bacterium of STSS was not GAS, but SDSE of GGS.…”
Section: Discussionmentioning
confidence: 58%
“…Among GGS, SDSE infection is most frequent in humans [5]. While STSS due to GAS can occur in patients without underlying conditions [6], STSS due to GGS tends to occur in elderly patients and those with underlying conditions, such as diabetes mellitus, cardiovascular diseases, malignancies, cirrhosis, immunosuppressive conditions, or skin diseases [5,7,8]. In our case, the causative bacterium of STSS was not GAS, but SDSE of GGS.…”
Section: Discussionmentioning
confidence: 58%
“…Nineteen studies reported information on antimicrobial susceptibility testing. In fifteen of them, all tested isolates were 100% susceptible to penicillin [ 2 , 22 , 24 , 28 , 31 , 36 , 40 , 42 44 , 46 , 47 , 51 , 54 , 55 ]. Four studies reported some resistance to penicillin [ 23 , 27 , 30 , 35 ], at 2%, 1.4%, 0.5%, and 2%, respectively ( S5 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…For the few settings where comparative epidemiologic data are available, the incidence of iGCGS infection is similar or higher than for invasive GAS (10,11). Also shared in common with invasive GAS infections, iGCGS has a death rate of 5%-10%, and its incidence appears to be increasing in recent years in some countries (10,(12)(13)(14).In a recent study, we demonstrated an increasing incidence of invasive GAS infection that disproportionately affects Indigenous Australians (15). By using this same methodology, we sought to describe the epidemiology of iGCGS infection in terms of incidence, median length of hospital stay, and all-cause deaths and to compare these metrics with those in patients with invasive GAS infections.…”
mentioning
confidence: 87%
“…Unlike GAS, which is notifiable in many jurisdictions, such as the United Kingdom (8) and Canada (9), iGCGS is not considered a notifiable disease in any jurisdiction. For the few settings where comparative epidemiologic data are available, the incidence of iGCGS infection is similar or higher than for invasive GAS (10,11). Also shared in common with invasive GAS infections, iGCGS has a death rate of 5%-10%, and its incidence appears to be increasing in recent years in some countries (10,(12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation